Relevance of iron metabolic genes in biofilm and infection in uropathogenic Proteus mirabilis - Iribarnegaray, V; González, MJ; Caetano, AL; Platero, R; Zunino, P; Scavone, P (Current research in microbial sciences, 2021)
•Proteus mirabilis cause catheter associated urinary tract infections with severe complications for patients.•Iron metabolism is relevant for surviving in the limited conditions of the urinary tract.•Non-hem ferritin and TonB-dependent receptor are relevant for biofilms formation and infection. The microorganisms are found in the environment, forming sessile communities embedded in an extracellular matrix of their own production, called biofilm. These communities have a great relevance in the clinical context, since they are associated with infections caused by biofilm in medical implants, such as urinary catheters. The development of biofilms is a complex process where a great diversity of genes participate. The present work is based on the study of genes related to iron metabolism and its implication in the development of P. mirabilis biofilms and pathogenicity. For this study, two mutant strains defective in biofilm formation were selected, generated by the interruption of genes that encoded non-heme ferritin and TonB-dependent receptor. The mutations influence on the development of the biofilm was evaluated by different approaches. The complexity of the biofilm was analyzed using Confocal Laser Microscopy and image analysis. The mutants infectivity potential was assessed in two experimental mice models of urinary tract infection. The results obtained in the present work show us the role of the ferritin and a TonB-associated porin protein over the initial and later stages of biofilm development. Moreover, in the ascending UTI mouse model, both mutants failed to colonize the urinary tract. In CAUTI models, ferritin mutant damaged the bladder similarly to wild type but the Ton-B mutant was unable to generate infection in the urinary tract. The results obtained in the present work confirm the relevant role that iron metabolism genes have in P. mirabilis biofilm development and for infection in the urinary tract.